Is manufacturing still the engine of growth? A multi sector analysis with a common correlated effects approach - Silva, Caíque Ferreira (2021)
Since the middle of the twentieth century manufacturing has been assumed as an engine of economic growth and development. Nevertheless, the most recent literature has been pointing to other sectors, such as services, as the locus of productivity gains. This dissertation work access the role of manufacturing in the economic growth in 41 developed and developing countries between 1960 and 2010, adding services and two of its sub-sectors into the analysis. We propose the Common Correlated Effects method, developed by Pesaran (2006), for both static and dynamic panels, finding that these effects are present in the data. Moreover, the results indicate that manufacturing is indeed an engine of growth in the static panel data models, but have no growth impact with the dynamic panel approach.